Employers’ Perceptions On Algerian English Major Graduates’ Soft Skills: Djelfa Private Schools Case Study - Maria Hassani; Sarah Meharet (The Journal of Studies in Language, Culture and Society)
The transition of English major graduates into the job market poses significant challenges. According to prior research, the lack of the required soft skills underlies those defies. However, scant or no attention is paid to the perspectives of employers regarding English as a Foreign Language (EFL) graduates’ soft skills. To address this gap, this study aims to investigate employers’ perceptions on Algerian EFL graduates' soft skills in the district of Djelfa. To this end, employers from 23 private schools participated in this study. Through a mixed-approach design, they filled out structured questionnaires and partook in interviews. The findings signal a discernible misalignment between employer expectations and the actual soft skill levels of EFL graduates. This mismatch accentuates the pressing need for closer harmonization between educational curricula and industry requisites. Furthermore, employers advocate for bolstering soft skills through targeted educational interventions, training initiatives, and harnessing the potential of Artificial Intelligence. This study spotlights the imperative for concerted efforts to bridge the gap between academia and industry.